Potential Links between Hepadnavirus and Bornavirus Sequences in the Host Genome and Cancer - Honda, Tomoyuki (Frontiers in Microbiology, 2017)
Various viruses leave their sequences in the host genomes during infection. Such events occur mainly in retrovirus infection but also sometimes in DNA and non-retroviral RNA virus infections. If viral sequences are integrated into the genomes of germ line cells, the sequences can become inherited as endogenous viral elements (EVEs). The integration events of viral sequences may have oncogenic potential. Because proviral integrations of some retroviruses and/or reactivation of endogenous retroviruses are closely linked to cancers, viral insertions related to non-retroviral viruses also possibly contribute to cancer development. This article focuses on genomic viral sequences derived from two non-retroviral viruses, whose endogenization is already reported, and discusses their possible contributions to cancer. Viral insertions of hepatitis B virus play roles in the development of hepatocellular carcinoma. Endogenous bornavirus-like elements, the only non-retroviral RNA virus-related EVEs found in the human genome, may also be involved in cancer formation. In addition, the possible contribution of the interactions between viruses and retrotransposons, which seem to be a major driving force for generating EVEs related to non-retroviral RNA viruses, to cancers will be discussed. Future studies regarding the possible links described here may open a new avenue for the development of novel therapeutics for tumor virus-related cancers and/or provide novel insights into EVE functions.